(untitled) (Journal of Open Law, Technology & Society, 2010)
HTML5 is an updated version of the hypertext markup language that has been empowering the World Wide Web for the last 20 years. One of the things that HTML5 introduces is a element, which make video content as simple to include into Web pages as images. Similar to the issues that had to be overcome with the introduction of the tag in 1993, we are now facing the issue of a common baseline codec for the element – a format that all browser vendors can implement from a rights point of view and will agree to implement. Ogg Theora/Vorbis has been proposed as a solution, but only Mozilla Firefox and Google Chrome have agreed to that implement it. Right now, we are at an impasse as the patent situation around video codecs is unclear and different parties take a different stance. This article discusses the issues in more detail.